Braving the Storm : Poverty and Inequality in Bosnia and Herzegovina 2007-2011 - World Bank (World Bank, Washington, DC, 2015)
This note describes the trends in, and composition of, absolute poverty based on household expenditures, and is thus concerned, as a matter of policy objectives, with access of the population to a particular minimum standard of living. This should be viewed as complementary to the companion note on social exclusion based on Europe 2020 indicators including the relative at-risk-of-poverty (AROP) rate, focuses on low income in relation to other residents in a given country. In addition to the analysis of absolute poverty, the note also presents an analysis of inclusive growth, aimed at assessing whether income growth (losses) benefit (impact) differentially the lowest part (here, bottom forty percent) of the distribution. Other approaches, such as those including measures of poverty based on current income, or self-reported measures of affordability, or approached that differ in the way they set the poverty threshold exist. The choice of World Bank’s methodology for purposes of this report is primarily on pragmatic grounds: (i) it allows for the analysis of trends during 2007-2011; (ii) the same methodology was adopted in the previous report (World Bank 2009) to analyze poverty trends during 2004-2007, thus providing a longer trend; (iii) it allows for comparisons of trends across the entities of BiH.